Absolute Volume Deformation Potentials of Inorganic ABX3 Halide Perovskites: The Chemical Trends. Issue 6 (21st April 2021) - Wang, Shanshan; Huang, Menglin; Wu, Yu‐Ning; Chen, Shiyou
Abstract: The absolute volume deformation potential (AVDP) is an important physical quantity that describes the absolute energy level shift of semiconductors under pressure. The valence band maximum (VBM) and conduction band minimum (CBM) AVDPs of inorganic cubic ABX3 perovskites (where A = K, Rb, Cs; B = Ge, Sn, Pb; X = Cl, Br, I) are systematically investigated using ab‐initio simulations. Spin‐orbit coupling (SOC) is found to have negligible effect on the AVDPs of ABX3 perovskites, though it plays an important role in their band structures. The AVDPs of VBM are determined to be all negative and large, meaning the energy level will shift downward as the crystal volumes increase, while AVDPs of CBM are mostly positive and small. The AVDPs of VBM and CBM both increase as the atomic number of X‐site element increases, while the absolute value of VBM's AVDP increases initially and decreases afterward as atomic number of B‐site element becomes larger. These trends can be well explained based on the atomic orbital levels, the hybridization of the band edge orbitals, bond length, and bandwidth. These results provide critical parameters for the band structure engineering design of optoelectronic devices based on the ABX3 halide perovskites through strain control. Abstract : In heterostructures synthesized from all‐inorganic halide perovskites, strain effect exists inevitably and tunes the electronic structure of semiconductors, such as, band edges, which can be evaluated by the absolute volume deformation potential (AVDP). The AVDPs of valence band maximum and conduction band minimum of ABX3 ‐type inorganic perovskites are systematically investigated and chemical trends of their properties are analyzed.